2000
DOI: 10.1037/0893-164x.14.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Progression of consequences among heavy-drinking college students.

Abstract: Among a sample of 180 male and 226 female undergraduates, 84.2% reported a heavy drinking episode (5+ drinks for men, 4+ for women) within the previous 90 days. Principal-components analysis revealed 3 alcohol-related problem factors among the heavy drinkers (Careless Behavior, Risky/Reckless Behavior, and Authority Problems). Nearly all heavy drinkers experienced a careless behavior that was due to drinking (92.7%), and many reported a risky/reckless behavior (60.2%), yet only one third (33.9%) experienced an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 36 publications
5
55
0
1
Order By: Relevance
“…unintentional injury, driving or committing assault or sexual assault whilst intoxicated, engaging in unplanned or unprotected sexual activity) have become increasingly prevalent in a University population (Hingson, Heeren, Winter, & Wechsler, 2005;Hingson et al, 2003;Vik, Carrello, Tate, & Field, 2000). However, the majority of research measuring the range and type of alcohol-related harms in a University student population has been conducted in the United States of America (USA), a drinking culture that varies in subtle but important ways to the UK.…”
Section: Resultsmentioning
confidence: 99%
“…unintentional injury, driving or committing assault or sexual assault whilst intoxicated, engaging in unplanned or unprotected sexual activity) have become increasingly prevalent in a University population (Hingson, Heeren, Winter, & Wechsler, 2005;Hingson et al, 2003;Vik, Carrello, Tate, & Field, 2000). However, the majority of research measuring the range and type of alcohol-related harms in a University student population has been conducted in the United States of America (USA), a drinking culture that varies in subtle but important ways to the UK.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, national survey data from approximately 14,000 students indicate that 44% of students report binge drinking, defined as 5 or more drinks in a row for males and 4 or more for females, at least once in the past 2 weeks, with 23% of those reporting binge drinking three or more times in the past 2 weeks (Wechsler, Lee, Kuo, & Lee, 2000). Further, heavy drinking is associated with multiple social and interpersonal problems such as arguing with friends, engaging in unplanned sexual activity, drinking and driving, getting into trouble with the law, academic difficulties, unintended injuries, assault, and death (Abbey, 2002;Cooper, 2002;Hingson, Heeren, Zakocs, Kopstein, & Wechsler, 2002;Hingson, Heeren,Winter, & Wechsler, 2005;Perkins, 2002;Vik, Carrello, Tate, & Field, 2000;Wechsler et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some individuals progress from more common and presumably less severe problems to more extreme consequences (Nelson et al, 1996;Vik et al, 2000), and unique consequence types have recently been shown to differentially predict future drinking outcomes (Read et al, 2013). Furthermore, problems that are on the more severe end of the continuum (e.g., impaired control, physiological dependence) are associated with particularly poor long-term outcomes (Chung and Martin, 2002;Nagoshi, 1999;O'Neill and Sher, 2000).…”
mentioning
confidence: 99%